The Financial Management of Early Childhood Education (PAUD): An Analytical Study of Funding Sources, RAPBS Preparation, and Financial Accountability - Nadya Dwie Islami; Nabila Iffatul Maula; Shifa Galuh Chandraningtyas; Khoirun Nisa; Asqia Viani; Fahmi (Al-Qalam Institue, 2026)
Financial management in Early Childhood Education (PAUD) institutions is essential for ensuring sustainability and improving educational quality. However, challenges such as limited funding, weak financial administration, and lack of transparency are still common. This study aims to analyze the financial management cycle in PAUD, including funding sources, budgeting (RAPBS), implementation, and accountability. This research uses a qualitative approach with a library research method, drawing data from books, journals, and relevant documents. Data were analyzed using descriptive qualitative techniques. The findings indicate that effective financial management must be based on principles of transparency, accountability, efficiency, effectiveness, and participation. A systematic budgeting process, proper financial administration, and transparent reporting enhance public trust and institutional sustainability. Therefore, improving managerial competence and adopting adaptive financial systems are necessary to optimize financial governance in PAUD institutions.